Arthropod diversity and trophic balance in monoculture and polyculture rice fields in Mardingding, Karo, North Sumatra, Indonesia - TRI YANINTA GINTING; HERMANU TRIWIDODO; I WAYAN WINASA; NINA MARYANA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ginting TY, Triwidodo H, Winasa IW, Maryana N. 2026. Arthropod diversity and trophic balance in monoculture and polyculture rice fields in Mardingding, Karo, North Sumatra, Indonesia. Biodiversitas 27 (5): d270502. https://doi.org/10.13057/biodiv/d270502. This study evaluated the temporal dynamics and functional balance of arthropod communities in monoculture and polyculture rice systems across two cropping seasons in Mardingding Sub-district, Karo District, North Sumatra, Indonesia. Polyculture refers to rice fields in which diversification was implemented primarily through companion vegetation on bunds or surrounding field margins, whereas monoculture consisted of rice grown without such border vegetation. Weekly arthropod sampling was conducted from planting to harvest in six farmer-managed paddy fields using a portable suction sampler. Arthropods were identified as morphospecies and classified into functional guilds. Community structure was assessed using Shannon-Wiener diversity (H′), Pielou's evenness (E), and Simpson's dominance (D) indices and analyzed using GLM repeated-measures ANOVA, in which fields were treated as independent experimental units (n: 6), temporal observations were modeled as repeated measures within fields, and cropping season was included as a within-subject factor. Temporal patterns showed that diversity and evenness increased toward mid-season and declined near crop maturity, whereas dominance showed the opposite trend. The cropping system had a significant effect on diversity (F(1, 4): 18.86, p: 0.012, partial η2: 0.825), whereas the cropping season was not (p: 0.095). The interaction between the cropping system and season was also not significant. Evenness was significantly influenced by cropping season (F(1, 4): 12.44, p: 0.024, partial η2: 0.757), while no significant effects were detected for dominance. Paired comparisons at the field level indicated higher diversity in polyculture during Season 1, whereas differences were not significant in Season 2. Polyculture fields also showed higher natural enemy-to-pest ratios than monoculture. These findings suggest that crop diversification through bund-associated vegetation was associated with a higher relative abundance of natural enemies and may contribute to shifts in trophic structure within rice agroecosystems.